2022
DOI: 10.1186/s12992-022-00899-1
|View full text |Cite
|
Sign up to set email alerts
|

“Won’t get fooled again”: statistical fault detection in COVID-19 Latin American data

Abstract: Background Claims of inconsistency in epidemiological data have emerged for both developed and developing countries during the COVID-19 pandemic. Methods In this paper, we apply first-digit Newcomb-Benford Law (NBL) and Kullback-Leibler Divergence (KLD) to evaluate COVID-19 records reliability in all 20 Latin American countries. We replicate country-level aggregate information from Our World in Data. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
0
0
1
Order By: Relevance
“…Similarly, our analysis identified notable departures from the expected distribution in the dengue cases dataset, supporting the presence of potential anomalies or irregularities. Another relevant study by Figueiredo Filho et al (2022) examined the application of NBL in detecting data fraud in COVID-19 statistics. Their research revealed deviations from the expected distribution in certain countries' reported COVID-19 data, suggesting possible data irregularities.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our analysis identified notable departures from the expected distribution in the dengue cases dataset, supporting the presence of potential anomalies or irregularities. Another relevant study by Figueiredo Filho et al (2022) examined the application of NBL in detecting data fraud in COVID-19 statistics. Their research revealed deviations from the expected distribution in certain countries' reported COVID-19 data, suggesting possible data irregularities.…”
Section: Discussionmentioning
confidence: 99%
“…Aunque la tasa de letalidad por semana epidemiológica es una de las medidas más específicas para calibrar si la pandemia está llegando a su fin, otras son la incidencia de contagios, el índice de positividad, el comportamiento estacional de los brotes, las tasas de vacunación, la disponibilidad de 93-102 tratamientos eficaces y la capacidad de transmisibilidad de las variantes actuales y nuevas sub variantes que van surgiendo del Covid-19 5,6 . Lamentablemente la falta de datos sistematizados de muchos países genera incertidumbre y confusión al momento de analizar los datos 7,8 , por ello en algunos países es difícil establecer si se continua en la fase aguda de la pandemia o en su defecto ya se encuentra en una fase endémica, que implicaría la ausencia de grandes brotes nuevos por Covid-19.…”
unclassified